Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/09567976221074650
|View full text |Cite
|
Sign up to set email alerts
|

Cultures Crossing: The Power of Habit in Delaying Gratification

Abstract: Resisting immediate temptations in favor of larger later rewards predicts academic success, socioemotional competence, and health. These links with delaying gratification appear from early childhood and have been explained by cognitive and social factors that help override tendencies toward immediate gratification. However, some tendencies may actually promote delaying gratification. We assessed children’s delaying gratification for different rewards across two cultures that differ in customs around waiting. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 48 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…For example, in their study of delay of gratification in Japanese and US preschoolers, Yanaoka et al. (2022) used both the traditional marshmallow task in conjunction with the same task with wrapped gifts as prizes instead of the marshmallow. Although Japanese children waited to eat the marshmallow, US children more easily waited to open a wrapped gift.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in their study of delay of gratification in Japanese and US preschoolers, Yanaoka et al. (2022) used both the traditional marshmallow task in conjunction with the same task with wrapped gifts as prizes instead of the marshmallow. Although Japanese children waited to eat the marshmallow, US children more easily waited to open a wrapped gift.…”
Section: Discussionmentioning
confidence: 99%
“…The child was told that if they waited until the experimenter returned to the room (7 min) they would receive the larger quantity of snack. However, if the child could not wait, they could ring a bell that would bring the experimenter back into the room and the for overlapping heavily with parenting, caregiver availability, household income and child expectation management (e.g., Watts et al, 2018), it remains a widely studied measure of cognitive control (e.g., Conway, 2020;Doebel et al, 2020;Kuhn et al, 2014;Jahromi et al, 2019;Protzko, 2020;Yanaoka et al, 2022) and relates to a range of outcomes across populations, including those implicated in cognitive variance (e.g., Li et al, 2022;de Water et al, 2021;Watts et al, 2018). Whether considered separately or as a core conceptual component of executive function, delay of gratification tasks remain an important predictor involved in inhibitory control and are available in the NICHD SECCYD dataset at the 4.5-year-old timepoint and subsequent timepoints.…”
Section: Self-regulationmentioning
confidence: 99%
“…To what extent this also applies to the values embedded within Indian educational contexts for young children needs to be explored in future research. Other factors to be explored include to what extent DG in preschoolers in India tend to be specific to types of reward used: Yanaoka et al (2022) , for example, found that children in Japan were more likely to show DG for food items than children in the United States, who in turn had longer waiting times for gifts than Japanese children. Eventual success in applying robotic technology in the teaching of DG ultimately depends on the ability to generate higher efficiency than what current approaches can offer.…”
Section: Discussionmentioning
confidence: 99%